Estimation of velocity at VO2max in well-trained swimmers - Almeida, T.; Espada, M.; Reis, J.; Bernardo, R.; Vleck, V.; Alves, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Maximal oxygen uptake (VO2max) has long been recognized as a poor performance determinant in high level competitive swimming. For specific training prescription, VO2max needs to be associated with performance parameters, particularly maximal aerobic velocity (vVO2max), which serves as a basis for individualizing the relative intensity of training. The use of mean velocity during a 400 m freestyle event (S400), or more accurately, the central 300 m mean velocity (MAV), has been identified as a predictor of vVO2max (Lavoie & Montpetit, 1986), and used extensively in training and research. However, race pacing strategies and other contextual factors may hinder its usefulness. The aim of the present study was to ascertain the prediction power of S400 or MAV for the estimation of vVO2max, determined by a standard incremental protocol. Methods: Fourteen competitive male swimmers completed an incremental test composed by 5x250 and 1x200 m front crawl for VO2max and vVO2max determination. Breath-by-breath gas exchange was measured throughout each test with a telemetric system (Cosmed K4b2, Rome, Italy), using the aquatrainer swimming snorkel® for expired gas collection. VO2 data were averaged every 15 s. Before each test, the oxygen analyzer system was calibrated according to the manufacturer`s instructions while the turbine flowmeter was calibrated using a 3-L syringe (Quinton Instruments, Wis., USA). The criteria used to define VO2max were a plateau in VO2 despite an increase in swimming velocity (SV) and a heart rate in excess of 90% of the predicted maximal heart rate. In this protocol of incremental exercise, vVO2max was defined as the lowest SV at which VO2max occurred, according to Billat & Koralsztein (1996). 800 and 400 m performances in a swimming competitive event were recorded, the latter for determination of S400 and MAV. Results: As expected, VO2max showed no association with performance, both in the 400 and the 800 m freestyle events. On the contrary, vVO2max could explain an important variation of performance at both distances (r = 0.66, p < 0.01 and r = 0.74, p < 0.01, respectively). vVO2max (1.44 ± 0.04 m/s) was significantly different from S400 (1.48 ± 0.04 m/s), but not from MAV (1.45 ± 0.04 m/s). However, adjusted r2 was only 0.6, with a SEE of 0.025, in spite of standardized residuals remaining within the 95% confidence interval limits, indicating a fairly good estimation model. Discussion: vVO2max can be estimated from MAV, but not from S400. The degree of accuracy of the model is acceptable for many training design and evaluation purposes. However, individual estimations should be done carefully.